Fostering Sustainable Practices through the Implementation of a Green Procurement Management System for IFAD Funded Economic Transformation Initiatives in Gilgit-Baltistan/Donor Funded projects - Muhammad Ali Baig; Abbas Ali; Ghulam Mustafa; Sajad Afzal; Syed Farrukh Hussain Shah; Shahid Hussain; Muhammad Ibrahim; Mubashir Hassan; Nasir Hussain (Indus Journal of Social Sciences, 2025)
This research project aims to explore and suggest the adoption of a Green Procurement Management System (GPMS) as a strategic tool for fostering sustainable practices in economic transformation initiatives funded by the International Fund for Agricultural Development (IFAD) in Gilgit-Baltistan. This study is set against the backdrop of IFAD's commitment to promoting inclusive and sustainable rural development, acknowledging the urgent need to reconcile development projects with environmental conservation. The project is significant because it aims to introduce and evaluate a specialized procurement system designed to meet the specific needs of IFAD-funded projects in Gilgit-Baltistan. This study is motivated by the acknowledgment of a dual responsibility: addressing environmental problems while promoting sustainable economic growth. It is essential to include green procurement practices that reduce environmental impact, as economic transformation initiatives can have far-reaching ecological effects. This study posits that a dedicated Green Procurement Management System is crucial for effectively managing the convergence of economic development and environmental stewardship, particularly in relation to IFAD's work in Gilgit-Baltistan. The project aims to achieve three objectives, the first of which is to set up a comprehensive Green Procurement Management System tailored to the specific needs of projects funded by IFAD; secondly, to assess how green procurement influences sustainable development in the region; and third, to extract recommendations that can lead and improve procurement practices for future IFAD initiatives. The study employs a mixed-methods approach, incorporating surveys, interviews, and document analysis, to ensure a nuanced understanding of the complex challenges and opportunities associated with integrating green procurement. The research is anticipated to lead to the development and adoption of a Green Procurement Management System tailored for IFAD-funded projects. Expected outcomes include a heightened awareness and understanding of green procurement practices among stakeholders, resulting in improved sustainability indicators across economic transformation initiatives. The research recognizes and tackles potential limitations, including time constraints, limited access to certain project documents, and external influences on the execution of green procurement. During the research, findings will be presented, analyzed, and synthesized to shed light on the effectiveness of the Green Procurement Management System. Stakeholder perceptions and engagement levels, as well as the identification of challenges and successes in integrating green procurement practices, will be thoroughly examined. The conclusion will recapitulate the key findings, reflect on their broader implications, and evaluate the scalability and replicability of the proposed GPMS. In summary, this study aims to provide guidance on how to effectively integrate green procurement practices into economic transformation initiatives in Gilgit-Baltistan that are funded by IFAD. The recommendations resulting from this study could revolutionize procurement practices, guaranteeing that economic development and environmental sustainability are harmoniously aligned in the pursuit of long-term, inclusive, and resilient rural transformation.